Application of ANSYS software package for electromagnetic and thermal analysis of the electric motor of the pilger mill drive seamless pipe manufacturing technology - B. I. Kosimov (Омский научный вестник)
Currently, the metallurgical production contains a large number of morally and physically outdated electrical equipment that requires modernization. Large capital expenditures are required to replace it. For this reason, it is slow to implement, long-term use for the purpose of payback, and slowly decommissioned. In this regard, the new equipment should be innovative and in many ways ahead of the existing level of development of the industry. The article offers such a solution for the company PJSC «Chelyabinsk pipe rolling plant». To replace the existing collector motor of the pilger mill drive for the manufacture of seamless pipes, which has been operating since 1928 and is in critical condition, a large-size low-speed valve motor with a large built-in inertial mass, having a permanent magnet magnetic system and claw-poles, is proposed to replace the existing collector motor of the pilger mill drive for the manufacturing of seamless pipes, which has been operating since 1928 and is in critical condition. Such a technical solution for drives of this class has not been used in the world. The motor eliminates the existing 120-ton flywheel, improves reliability due to contactless current supply, and reduces operating costs by eliminating excitation losses. The design of the engine allows its assembly without additional technological equipment, which is very important for large engines with permanent magnets. To develop a unique motor, a design system consisting of a synthesis subsystem and an analysis subsystem was created. The synthesis subsystem implements multi-level single-criteria optimization. As a result of its work, the optimal geometry is determined according to the selected criterion. The analysis system confirms the accuracy of the calculation using simplified optimization methods and finally removes technical risks before manufacturing an industrial design. It is based on the Ansys Electronics Desktop and Ansys Icepak systems that are well-developed for CAE electric machines. The analysis has several stages and includes electromagnetic and thermal analysis. The proposed design system is tested on a real project and implemented as a calculation of the magnetic and thermal state with dynamic load in JSC «Russian electric motors».